Building Virtual Bridges: How Rural Micro‐Enterprises Develop Social Capital in Online and Face‐to‐Face Settings. Issue 1 (20th November 2014) - Townsend, Leanne; Wallace, Claire; Smart, Alison; Norman, Timothy
Abstract: In rural UK, businesses are often isolated and have much to gain from healthy networks, yet studies show that many rural business owners fail to network effectively. Information communications technologies offer new ways to network that might benefit rural businesses by expanding their reach. This study looked at online and face‐to‐face networking behaviour among rural micro‐enterprises in Scotland in relation to the development of bonding and bridging social capital. Given the challenges of remoteness faced by many rural businesses, online networking is particularly useful in developing bridging capital, but is an unsuitable context for building the trust needed to gain tangible benefits. The article therefore highlights the importance of face‐to‐face interactions in developing trust and bonding social capital. Rural business owners face distinctive challenges with respect to online communications, which are explored in this article.